Pengaruh Pengetahuan Akuntansi, Skala Usaha Dan Ketidak Pastian Lingkungan Terhadap Penggunaan Informasi Akuntansi Di UMKM Sulaman Naras - Ananda, Rezi Febriawanti; Sulastri, Sulastri; Handayani, Deby (Universitas Sumatera Barat, 2022)
This research aims to analyze the influence of accounting knowledge, business scale and insight into the environment on the use of accounting information in Sulaman Naras MSMEs. This research uses descriptive analytical research with a quantitative approach. The sampling method used in the research was purposive sampling, resulting in a sample of 61 respondents. The data analysis used was multiple linear regression using the SPSS version 26 program. From the results of the regression test it was found that (a) a) there was no influence of Accounting Knowledge on the Use of Accounting Information, b) there was an influence of Business Scale on the Use of Accounting Information, c) there was the influence of Environmental Uncertainty on the Use of Accounting Information, d) there is an influence of Accounting Knowledge, Business Scale and Environmental Uncertainty on the Use of Accounting Information, based on the Adjust R Square value of 0.614 indicating that the contribution of the variables Accounting Knowledge, Business Scale and Environmental Uncertainty to the Use of Accounting Information is 0.714 or 71.4% while the remaining 28.6% is determined by other variables not explained in the model in this study.